Dissuasion: the Elaboration Likelihood Model and young children. Issue 3 (15th August 2016) - McAlister, Anna R.; Bargh, Danielle
Abstract : Purpose: The Elaboration Likelihood Model (ELM) proposes two routes to persuasion – the central route (persuasion occurs via information) and the peripheral route (persuasion occurs via visual cues, attractive actors and other source characteristics). The central route is typically used for high-involvement decisions and the peripheral route is used in low involvement situations. The ELM has received extensive support when tested with adults; however, its ability to explain young children's responses to persuasive communications has not been fully tested. Hence, the purpose of this research is to assess whether the standard tenets of the ELM apply to children's processing of persuasive messages. Design/methodology/approach: This study involved 84 preschool children, ages three to six. It used a 2 (involvement) × 2 (argument strength) × 2 (source attractiveness) design to test children's responsiveness to advertisements for a novel breakfast cereal. Findings: The findings suggest that children are naturally inclined to be persuaded by advertising messages, regardless of their level of involvement. It is the weak arguments and weak peripheral cues that dissuade children who are highly involved with a message. Originality/value: This research makes an original contribution to the existing literature by testing the extent to which the ELM applies to children's processing of persuasive advertisements. The finding that weak peripherals dissuade children from believing an ad's message has strong implications for advertising practitioners.